Comunicação através da arte e das novas tecnologias que renovam e complementam a renda familiar - Palhaci, Maria do Carmo Jampaulo Plácido [UNESP]; Hellmeister, Luiz Antonio Vasques [UNESP]; Barbis, Bianca [UNESP]; Leonardo Filho, Murilo Rodolfo Penteado [UNESP]; Pereira, Juliana Fernandes [UNESP] (My University, 2013)
Sustainability suggests a new social organization required for human survival. The aggravation of environmental problems arising by population growth, industrialization, disorderly and unconscious consumption of Human Being, induces us to think about how to stop these problems. Recycling presents itself as a means of stopping environmental destruction and as a way to increase the family income of the poorest society existing in our globalized world. This article suggests a research on recycling being carried out as a means of livelihood.
Keywords: Bibliographic references; Sustainability; Recycling